Imperfect Good and Evil: Savonarola, Soderini, and Machiavelli’s Excusing of Failure - Shufro, Zachary E. (Politikon: The IAPSS Journal of Political Science, 2018)
In his Discourses on the First Decade of Livy, Machiavelli relies upon the example of his Tuscan contemporaries to tease out an understanding of the role of evil intentions in the founding of a political state. Through the examples of the Perugino Giovampagolo Baglioni and the Florentines Girolamo Savonarola and Piero Soderini, Machiavelli implicitly defines good and evil intentions for founding a state, as well as the corresponding ‘good’ and ‘bad’ means through which such a state is founded. When Machiavelli examines the failings of these men considering their respective motivations and means, he advocates in favor of excusing the failures of those who failed to be ‘perfectly evil’ through willingness to act over those of one who failed to be ‘wholly good’ through passive acceptance. This advocacy, in turn, reveals Machiavelli’s belief in the expedient nature of deception in the foundation of a durable political order.